Canadian Two-Children Families: Factors Influencing - Adams, Wesley J. (Canadian Journal of Counselling and Psychotherapy, 2011)
Interviews were conducted in the homes of two-children families using a questionnaire format. A purposive sample was comprised of 200 parents which included both mothers and fathers. Significant correlations were found between wife's number of siblings, desired family size of both spouses, and future family size. However, no significant relationship was found between sex of children and preferred family size. This study suggests that while fertility decisions may be consciously made, one must be aware that past factors based primarily on one's spouse's experience may predominate the decision making process.